ABUNDANCES OF r-PROCESS ELEMENTS IN THE PHOTOSPHERE OF RED SUPERGIANT STAR PMMR23 IN SMALL MAGELLANIC CLOUD - Vasil'eva, S. V.; Gopka, V. F.; Yushchenko, A. V.; Andryevsky, S. M. (Одеські астрономічні публікації, 2017)
Detailed analysis of chemical abundances determined from high-resolution CCD-spectrogram of supergiant star PMMR23 (K5 I) in SMC is presented. The observation were obtained at 3.6 meter ESO La Silla telescope by Hill (1997). Spectral resolving power is near R=30.000. The wavelength coverage is 5050-7200 A. The abundances of iron and 15 r-, s-processes elements are found. The abundances of Cu, Zr, Mo, Ru, Pr, Sm, Gd, Dy, Er are found for the first time. The abundances of elements with atomic numbers less than 55 are deficient with respect to the Sun. The mean underabundance is near 0.7 dex. The abundances of barium and lanthanides are near solar values. The overabundances of these elements with respect to iron are in the range from 0.4 tp 0.9 dex. The abundances of heavy lanthanides are higher than the abundances of light lanthanides. The abundance pattern of PMMR23 can be fitted by scaled solar r- process distribution. The atmosphere of PMMR23 is enriched by r-process elements.